McPhee and party looks over Kellogg Ranch, 1948-1949 - Julian A. McPhee::::::::: (1948)
Documentation of Kellogg Ranch area, an 812-acre horse ranch, just at the time it was donated to Cal Poly by the W.K. Kellogg Foundation. Footage includes the then-president of Cal Poly, Julian McPhee, and presumably representatives from the Kellogg Foundation and other Cal Poly administrators. [00:00:15] A truck carrying men, including Cal Poly President Julian McPhee, drives up to a bluff overseeing the Kellogg Ranch [00:01:05] Shots of the truck driving around orchards [00:01:23] Several men gather around cattle [00:03:06] The men go into and come out of a building on the ranch [00:02:41] The men look at cows in a barn [00:02:59] End of recording